Bandau Agritrade - Irang, Apoi; Bohari, Muhamad Nazri; Abdul Rahman, Muhammad Faiz; Nordin, Mohammad Azrie; Roselim, Mohammad Shazwan (2018)
Bandau Agritrade is an existing farm dedicated to the production of fruits plant especially guavas. Bandau Agritrade has been formed as Kota Marudu-based company which located in Kampung Taginambur Baru, Kota Marudu. Bandau Agritrade is working hard to become a leading producer of botanical plants for (people) as well as plant nurseries. As for now Bandau Agritrade is focusing on guavas plants which have several types such as Seedless Guava, Jumbo Guava, Jumbo Rose Apple and many more.